Role of Triphala and Madhu in Oral Hygiene: A Clinical Study. - kaur, Paramjeet; Shukla, Amit Kumar; Mishra, Archna (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Dental caries and periodontal diseases are among the most important global oral health problems. In Ayurveda, Katu, Tikta and Kashaya Rasas are described for Dantadhawana. Most of the products available in the market are sweet in taste which favor the growth bacteria in of oral cavity whereas the Rasas mentioned in Ayurveda are supposed to suppress the growth of bacterial activity and resulting adverse effects on gums and teeth, thus the proposed formulation (Triphala, Madhu) is supposed to promote oral hygiene and restrict chances of gum and teeth disorders. Materials and methods: The role of Triphala churna with Madhu for Dantadhavana in healthy individuals was assessed. Results: The drug Triphla churna and Madhu plays a significant role in management of dental diseases as well as in maintaining healthy oral hygiene.